The complete mitochondrial genome of a tropical sea cucumber, Holothuria leucospilota. Issue 2 (3rd July 2019) - Cheng, Chuhang; Yu, Zonghe; Ren, Chunhua; Jiang, Xiao; Zhang, Xin; Wu, Xiaofen; Huang, Wen; Hu, Chaoqun
Abstract: The mitochondrial genome of Holothuria leucospilota was 15, 906 bp in length, containing 13 protein-coding genes (PCGs), 22 tRNA genes, and two rRNA genes. There were four initiation codons (ATG, ATT, ATC, and ATA) for the PCGs, and the termination codon of most PCGs was TAA, except for nad4 (TAG) and nad6 (TAG). Only one PCG ( nad6 ) and five tRNA genes ( tRNA Ser(UCN), tRNA Gln, tRNA Ala, RNA Val, and tRNA Asp ) were encoded on the light chain; the other genes were encoded on the heavy chain. H. leucospilota was most closely related to Holothuria scabra in a phylogenetic tree.